Why Deteriorating Relations, Xenophobia, and Safety Concerns Will Deter Chinese International Student Mobility to the United States - Allen, Ryan; Ye, Ying (Journal of International Students, 2021)
Collaborations between American and Chinese universities have been critical to global knowledge production. Chinese students accounted for over a third of all international students in the United States prior to COVID-19, but the pandemic paused most global mobility in 2020. We argue that this international mobility to the United States will not fully recover if larger stressors are left unaddressed. First, relations between the United States and China have deteriorated in recent years, especially under the Trump administration, with growing suspicion against Chinese researchers and scholars. Second, viral acts of violence and anti-Asian incidents have painted the United States as unsafe for Chinese students. Finally, given the mismanaged response to the pandemic, it may take years before trust returns from abroad. While the Biden administration has promised to curb some of these issues, the perceptions of the United States may have been permanently altered.